Geoeconomic potential of Kazakhstan is the basis of security and development of the country (Journal of Oriental Studies, 2022)
The article deals with The role of economic development in ensuring the stability of state independence comparative advantages in the international geoeconomic system in comparison with other countries after the transition of Kazakhstan to the latest market economic relations. Relative priority is the basis of the continuing geographical position between States and the development of diversity and integration processes in the natural resource, financial, transport, social, scientific and technical sectors. For Kazakhstan, in particular, the comparative priority-a key place and the transit potential located in the centre of the Eurasian giant space occupy the enormous natural-territorial and natural-resource potential. In addition, the preference for the country is the availability of production complexes formed in the Soviet Union and almost literacy of the entire population.